UMPSA students triumph at UTM Festival of Languages and Cultures (FLC) 2025 - Jamilah Bebe, Mohamad; Leong Hui, Theng; Amir Haikal Imran Ahmad Ashaari, Ahmad Ashaari (UMPSA, 2025)
JOHOR BAHRU, 14 May 2025 – Students from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) brought home two awards at Festival of Languages and Cultures (FLC) 2025 hosted by Universiti Teknologi Malaysia (UTM).